Strategi Pengembangan Usaha Kedai Kopi “Kandera Coffee” Denpasar Bali menggunakan Metode Swot dan QSPM - Damariyanti, Komang Listia; Hartiati, Amna; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
The rapid growth in the food and beverage service industry has also triggered the growth of new various concepts of business, one of which is the coffee shop. One of the coffee shop in Denpasar, namely Kandera Coffee, which has only been established since May 2020, doesn’t know yet the right strategy for developing their business. This study aims to determine the quadrant position of the Kandera Coffee shop when viewed through internal and external factors using the Internal-External Matrix and determine the appropriate priority development strategies for the the Kandera Coffee shop business. The methods used are SWOT and Quantitative Strategic Planning Matrix (QSPM). The research data were obtained from 5 expert respondents. The results showed that Kandera Coffee had 7 strengths, 5 weaknesses, 5 opportunities and 4 threats. Internal factors that influence the strength factor in the development of the Kandera Coffee business, namely the consistency of the taste of the product and service (0.29) and the weakness factor, namely the layout of Kandera Coffee shop is less ergonomic (0.13) and not very well known to the public (0, 13). While the external factors that influence the opportunity factor, namely build good relationship with customers (0.36) and the threat factors that influence, namely the level of coffee shop competitors is getting higher (0.34). The position of the Kandera Coffee shop is in cell V (five). This position is (hold and maintain) keep and maintaining with score the Interal Factor Evaluation (IFE) is (2.20) and External Factor Evaluation (EFE) is (2.56). Cell V consists of market penetration strategies and product development. The strategic priority order obtained based on the QSPM matrix is to provide the best service to customers (4,94), expand marketing on advertising and social media (4,87), improve product quality and maintain consistency of taste (4.63), develop a cozy coffee shop concept (4,61), give discounts to customers (4,59), and add a variety of coffee and food menus (4,10). Keywords :  business development strategy, coffee shop, Quantitative Strategic Planning Matrix (QSPM ), SWOT